Future optical networks: An optimised implementation of differential quadrature phase shift keying modulation format - Lee, L.H.; Geok, T.K.; Reza, A.W. (Natl Inst Optoelectronics, 2010)
This study proposes an optimised implementation of a differential quadrature phase shift keying (DQPSK) modulation format. The DQPSK scheme is an external modulation format, where modulators are needed for the generation of the optical signal for transmission. In this paper, the performance comparison between the conventional DQPSK modulation format and the optimised DQPSK modulation format is investigated. The obtained results and analysis show that the optimised DQPSK modulation format can achieve better performance as compared to the conventional DQPSK modulation format in terms of transmission distance. The technique presented in this study can help to increase the bandwidth and the speed of the optical fiber while maintaining the existing fiber cable and network facilities. This study can also assist the service providers to supply high-speed broadband services to the rural areas, which are located very far away from the central office.